1997
DOI: 10.1002/aic.690430518
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of initiation of incrustation

Abstract: Initiaton of incrustation by crystallization mechanisms is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Thus, there exists a combination of deterministic and stochastic processes occurring simultaneously. Similar processes occur during the fouling of tubular heat exchangers [38] and crystallizers [37]. While recognising the importance of agglomeration, this is not considered further in this article.…”
Section: Chemical Engineering Approach To Modelling Crystallization Imentioning
confidence: 94%
“…Thus, there exists a combination of deterministic and stochastic processes occurring simultaneously. Similar processes occur during the fouling of tubular heat exchangers [38] and crystallizers [37]. While recognising the importance of agglomeration, this is not considered further in this article.…”
Section: Chemical Engineering Approach To Modelling Crystallization Imentioning
confidence: 94%
“…Nucleation events in the bulk solution are mainly homogeneous nucleation and secondary nucleation triggered by seed crystals; nonetheless, secondary nucleation is the dominating nucleation mechanism in industrial crystallizers given the wide use of seeding, while homogeneous nucleation is negligible unless the crystallization process operates in the high supersaturation zone without seeding. In contrast, encrustation can be initiated through heterogeneous nucleation at the surface when local supersaturation is high or by adsorption of the crystals or crystal nuclei during collision onto solid surfaces at low local supersaturation levels. , Since the growth rates of the crystals and encrustation are expected to be similar for a given solution, competition between the nucleation mechanisms strongly affects the formation of encrustation. Many factors affect the rates of the different nucleation mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, encrustation can be initiated through heterogeneous nucleation at the surface when local supersaturation is high or by adsorption of the crystals or crystal nuclei during collision onto solid surfaces at low local supersaturation levels. 26,27 Since the growth rates of the crystals and encrustation are expected to be similar for a given solution, 1 competition between the nucleation mechanisms strongly affects the formation of encrustation. Many The rate at which encrustation forms and/or crystals grow depends on the nucleation and growth kinetics of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is found that at high supersaturation, the solid surface may initiate encrustation by catalyzing primary nucleation. Conversely, at a reasonably low supersaturation, collision of the crystals with the solid surface may initiate encrustation . Crystal nucleation, deposition, and growth may also occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%